The News Media in Raising Conflicts Tension: A Critical Study Toward News Conflict Between Israel and Palestine - AR, M Fikri (Tuturlogi: Journal of Southeast Asian Communication, 2024)
This study analyzes the news about conflict between Israel and Palestine in online news media Foxnews.com on May 2021. The characteristics of news from these news media have quite specific characteristics, which is a strong tone, using open visualization, inviting debate, and succeeding in getting thousands of comments from the audience. In this point, even though the news is read by many people, it is also has the potential to exacerbate conflict in the field. This study adopts Teun A. van Dijk’s Critical Discourse Analysis method which develops analysis from the microstructure, superstructure, and macrostructure levels. The micro structure level looks at the local meaning of the news text from the choice of diction, sentence structure, and rhetoric. Then, the super structure level examines the news scheme, consisting of introduction, content and conclusion. Furthermore, macro structural analysis tries to see the global meaning of news texts by looking at news topics and the surrounding social context. The results of the study show that the Israel and Palestine conflict is not only due to the conflict of one of the group carrying out the attack. But at the same time it was also caused by hard conflict news, there was trauma to the victims in the conflict, as well as the global security conditions still not stable until now.